Internalizing Multicultural Values through History Education: A Phenomenological Study at SMAS Tunas Markatin Jakarta - Andi Andi; Agus Mulyana; Wawan Darmawan; Murdiyah Winarti (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2026)
This study explores how students internalize multicultural values through history education in a diverse school context. Conducted at SMAS Tunas Markatin Jakarta, the research examines students’ understanding of tolerance, empathy, and cooperation within a learning environment that mirrors Indonesia’s plural society. Using a qualitative phenomenological approach, data were collected through in-depth interviews, classroom observations, and document analysis involving 20 students and three history teachers. The findings show that students at SMAS Tunas Markatin Jakarta have begun to internalize multicultural values through daily interactions that reflect respect, cooperation, and empathy. Their tolerance is evident in behaviors such as honoring peers’ religious practices and collaborating across ethnic and religious lines. Acts of mutual support during moments of personal difficulty further illustrate emerging social empathy. However, students’ understanding of multiculturalism remains mostly behavioral and has not yet developed into deeper reflective awareness. The school’s heterogeneous composition provides authentic opportunities for cross-cultural engagement that strengthen the internalization of values. History lessons emphasizing national unity help reinforce students’ appreciation of Indonesia’s plural identity. However, reliance on memorization and teachers' limited ability to connect historical content with contemporary diversity issues constrain deeper learning. Additionally, the absence of inclusive learning materials and school practices that favor the majority continues to pose significant challenges.